Relative neurotoxicity of ivermectin and moxidectin in Mdr1ab (-/-) mice and effects on mammalian GABA(A) channel activity. - Cécile Ménez; Jean-François Sutra; Roger Prichard; Anne Lespine (Public Library of Science (PLoS), 2012)
The anthelmintics ivermectin (IVM) and moxidectin (MOX) display differences in toxicity in several host species. Entrance into the brain is restricted by the P-glycoprotein (P-gp) efflux transporter, while toxicity is mediated through the brain GABA(A) receptors. This study compared the toxicity of IVM and MOX in vivo and their interaction with GABA(A) receptors in vitro. Drug toxicity was assessed in Mdr1ab(-/-) mice P-gp-deficient after subcutaneous administration of increasing doses (0.11-2.0 and 0.23-12.9 µmol/kg for IVM and MOX in P-gp-deficient mice and half lethal doses (LD(50)) in wild-type mice). Survival was evaluated over 14-days. In Mdr1ab(-/-) mice, LD(50) was 0.46 and 2.3 µmol/kg for IVM and MOX, respectively, demonstrating that MOX was less toxic than IVM. In P-gp-deficient mice, MOX had a lower brain-to-plasma concentration ratio and entered into the brain more slowly than IVM. The brain sublethal drug concentrations determined after administration of doses close to LD(50) were, in Mdr1ab(-/-) and wild-type mice, respectively, 270 and 210 pmol/g for IVM and 830 and 740-1380 pmol/g for MOX, indicating that higher brain concentrations are required for MOX toxicity than IVM. In rat α1β2γ2 GABA channels expressed in Xenopus oocytes, IVM and MOX were both allosteric activators of the GABA-induced response. The Hill coefficient was 1.52±0.45 for IVM and 0.34±0.56 for MOX (p<0.001), while the maximum potentiation caused by IVM and MOX relative to GABA alone was 413.7±66.1 and 257.4±40.6%, respectively (p<0.05), showing that IVM causes a greater potentiation of GABA action on this receptor. Differences in the accumulation of IVM and MOX in the brain and in the interaction of IVM and MOX with GABA(A) receptors account for differences in neurotoxicity seen in intact and Mdr1-deficient animals. These differences in neurotoxicity of IVM and MOX are important in considering their use in humans.